2021
DOI: 10.1155/2021/9590859
|View full text |Cite
|
Sign up to set email alerts
|

The Success Rate of Endotracheal Intubation in the Emergency Department of Tertiary Care Hospital in Ethiopia, One-Year Retrospective Study

Abstract: Background. Emergency medical care starts with airway assessment and intervention management. Endotracheal intubation is the definitive airway management in the emergency department (ED) for patients requiring a definitive airway. Successful first pass is recommended as the main objective of emergency intubation. There exists no published research regarding the success rates or complications that occur within Ethiopian hospitals emergency department intubation practice. Objective. This study aimed to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Our results showed that 85.7% of patients were intubated successfully on the first attempt. This rate compares favorably to ED intubations in other countries, which range from 70.3 to 85% in several studies (2,(22)(23)(24). Unsurprisingly, physicians with greater intubation experience were associated with a higher intubation success rate.…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that 85.7% of patients were intubated successfully on the first attempt. This rate compares favorably to ED intubations in other countries, which range from 70.3 to 85% in several studies (2,(22)(23)(24). Unsurprisingly, physicians with greater intubation experience were associated with a higher intubation success rate.…”
Section: Discussionmentioning
confidence: 66%
“…M Wongyingsinn et al at Siriraj Hospital revealed that 7 people received endotracheal intubation over a year [ 27 ]. Notably, 79.5% of these intubations were effective on the first try, making 99.6% successful [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…However multiple studies have shown ketamine as safe alternative. (12,13,17) The choice of induction drugs depends on the intubating physicians,\ their familiarity with the drug and clinical factors such as comorbidities and vital signs at the time of intubation such as avoiding propofol and midazolam in hypotension. (10,13,17) Paralytic agents minimize complications and improve chance of rst pass success during RSI.…”
Section: Resultsmentioning
confidence: 99%